Representasi Makna Kehidupan dalam Puisi di Selat Suba Karya Bara Pattyradja: Kajian Semiotik: Representation of the Meaning of Life in the Poem in the Suba Strait by Bara Pattyradja: A Semiotic Study - Mare, Fransiska Jone; Abel, Christiyanti; Maran, Alfonsus Duru (Information Technology and Science(ITScience), 2025)
This research is entitled Representation of the Meaning of Life in the Poem Di Selat Suba. The meaning of life, in this case, is in the form of character education that can be applied to everyday life, such as believing in God Almighty, tolerance, and love for the environment. The theory used in studying the poem by Bara Pattyradja is Roland Barthes's semantic theory. This theory emphasises the analysis of the meaning of signs that refer to the signifier and the signified. This study aims to find the meaning of denotation, connotation and myth. The qualitative descriptive method was used in this study to find the research objectives in a structured manner. After all the data was collected, the data began to be analysed using data triangulation techniques, namely data reduction, data presentation and conclusion. Based on the results of the data analysis, it was found that (1) the denotative meaning in this poem refers to life choices, awareness and certainty of death. The denotative meaning in this poem is very minimal. (2) This poem's connotative or figurative meaning refers to this life like a ship, flanked by choices, humans like fish, pleasure, emptiness, futility, prayer, and hope. Conscience and reason are guides in life. This poem generally uses connotative meaning, so it needs to be read repeatedly to understand the intended meaning. (3). The regional or mythical meaning refers to the name of the strait on Adonara Island, Selat Suba, and the complainer or Guangxi.